Mothers’ Knowledge about Speech and Language Development in Children Aged 0–3 Years: A Study at Helen K. Br Tarigan Clinic in 2024 - Rahmah, Lili Fitriati; Sinaga, Desriati; Br Sebayang, Emiya Bebiyona (LLDIKTI Wilayah 1, 2025)
Speech and language development is a crucial aspect of early childhood growth, allowing children to communicate, express thoughts, and interact with their environment. Delays in speech can have significant impacts on a child's academic performance and social interactions. Speech delay refers to a condition in which a child's verbal abilities do not align with developmental milestones. Various internal and external factors contribute to this issue, including genetics, family interaction, and parental knowledge. This study aims to describe the level of maternal knowledge regarding speech and language development in children aged 0–3 years, specifically among mothers with 2-year-old children at Midwife Helen K. Br Tarigan’s practice. This descriptive study involved 30 respondents selected through purposive sampling. Data were collected using a validated questionnaire and analyzed using univariate analysis. The results showed that most mothers (86.6%) had a low level of knowledge regarding speech and language development, indicating the need for increased health education and routine counseling by healthcare providers.